Using Detailed Single-star and Binary-evolution Models to Probe the Large Observed Luminosity Spread of Red Supergiants in Young Open Star Clusters - Chen Wang; Lee Patrick; Abel Schootemeijer; Selma E. de Mink; Norbert Langer; Nikolay Britavskiy; Xiao-Tian Xu; Julia Bodensteiner; Eva Laplace; Ruggero Valli; Alejandro Vigna-Gómez; Jakub Klencki; et al. (The Astrophysical Journal Letters, 2025)
Red supergiants (RSGs) represent a late evolutionary stage of massive stars. Recent observations reveal that the observed luminosity range of RSGs in young open clusters is wider than expected from single-star evolution models. Binary evolution effects have been suggested as a possible explanation. Here, we analyze 3670 detailed binary-evolution models, as well as corresponding single-star models, to probe the contribution of binary mass transfer and binary mergers to the luminosity distribution of RSGs in star clusters with ages up to 100 Myr. We confirm that the expected luminosity range of RSGs in a coeval population can span a factor of 10, as a consequence of mergers between two main-sequence stars, which reproduces the observed RSG luminosity ranges in rich clusters well. While the luminosity increase as consequence of mass transfer is more limited, it may help to increase the number of overluminous RSGs. However, our results also demonstrate that binary effects alone are insufficient to account for the number of RSGs found with luminosities of up to 3 times those predicted by current single-star models. We discuss observational accuracy, rotational mixing, age spread, and intrinsic RSG variability as possible explanations. Further observations of RSGs in young open clusters, in particular studies of their intrinsic brightness variability, appear crucial for disentangling these effects.